Detection of impulsive sounds in stream of audio signals - Suliman A.; Omarov B.; Dosbayev Z. (Institute of Electrical and Electronics Engineers Inc., 2023)
Audio systems; Data streams; Security systems; Signaling; Support vector machines; Video cameras; Video recording; Analytics systems; Automatic Detection; Computing power; Impulsive sounds; Maintenance cost; Security cameras; Urban surveillance; Video analytics; Audio acoustics